Review and comparison of quality standards, guidelines and regulations for laboratories - Tjeerd A.M. Datema; Linda Oskam; Paul R. Klatser (AOSIS, 2011)
Background: The variety and number of laboratory quality standards, guidelines and regulations (hereafter: quality documents) makes it difficult to choose the most suitable one for establishing and maintaining a laboratory quality management system. Objectives: There is a need to compare the characteristics, suitability and applicability of quality documents in view of the increasing efforts to introduce quality management in laboratories, especially in clinical diagnostic laboratories in low income and middle income countries. This may provide valuable insights for policy makers developing national laboratory policies, and for laboratory managers and quality officers in choosing the most appropriate quality document for upgrading their laboratories. Method: We reviewed the history of quality document development and then selected a subset based on their current use. We analysed these documents following a framework for comparison of quality documents that was adapted from the Clinical Laboratory Standards Institute guideline GP26 Quality management system model for clinical laboratory services. Results: Differences were identified between national and international, and non-clinical and clinical quality documents. The most salient findings were the absence of provisions on occurrence management and customer service in almost all non-clinical quality documents, a low number of safety requirements aimed at protecting laboratory personnel in international quality documents and no requirements regarding ethical behaviour in almost all quality documents. Conclusion: Each laboratory needs to investigate whether national regulatory standards are present. These are preferred as they most closely suit the needs of laboratories in the country. A laboratory should always use both a standard and a guideline: a standard sums up the requirements to a quality management system, a guideline describes how quality management can be integrated in the laboratory processes.